2012
DOI: 10.1021/ac202755e
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Support Vector Machines in the LIBS Toolbox for Sensitive and Robust Classification Amidst Unexpected Sample and System Variability

Abstract: Despite the intrinsic elemental analysis capability and lack of sample preparation requirements, laser-induced breakdown spectroscopy (LIBS) has not been extensively used for real world applications, e.g. quality assurance and process monitoring. Specifically, variability in sample, system and experimental parameters in LIBS studies present a substantive hurdle for robust classification, even when standard multivariate chemometric techniques are used for analysis. Considering pharmaceutical sample investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(67 citation statements)
references
References 45 publications
2
65
0
Order By: Relevance
“…Additionally, such studies in the later stages of development will also require the identification and systematic characterization of less common types of lesions not observed in the initial investigations here. Depending on the number of classes required and the complexity of the tissue biochemical composition, we will also assess the performance of other classification algorithms, such as soft independent modeling class analogy [32] and support vector machines [33]. Our long-term goal is to evaluate and translate Raman spectroscopy not only for the real-time detection of cancerous lesions but to be able to discriminate between the grades and stages of such tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, such studies in the later stages of development will also require the identification and systematic characterization of less common types of lesions not observed in the initial investigations here. Depending on the number of classes required and the complexity of the tissue biochemical composition, we will also assess the performance of other classification algorithms, such as soft independent modeling class analogy [32] and support vector machines [33]. Our long-term goal is to evaluate and translate Raman spectroscopy not only for the real-time detection of cancerous lesions but to be able to discriminate between the grades and stages of such tumors.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the experimental setup used for recording the data can be found in literature 5,8,31 , with the exception of the distance of the sample from the focussing lens. In brief, 532 nm laser pulses of 7 ns pulse duration from a Q-switched Nd: YAG were employed.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that with the application of various chemometric algorithms, it is possible to distinguish the similar type of materials based on their LIBS spectra. Different methods like soft independent modelling of class analogy (SIMCA) 3 , partial least squares -discriminate analysis (PLS-DA) 28,29 , support vector machines (SVM) 30,31 and artificial neural networks (ANN) 32,33 etc. have been successfully implemented for the classification of a wide variety of materials.…”
Section: Introductionmentioning
confidence: 99%